Study of the provenance and technology of asian kris daggers by application of X-ray analytical techniques and hardness testing - Nečemer, Marijan (Acta chimica slovenica, 2013)
Museum objects, such as the daggers presented in this study, contain a wealth of information regarding their role in certain historic periods, their potential users, the art of manufacture, the type of material used etc. Utilization of various modern instrumental techniques facilitates compositional information about the unknown artifact under investigation. In this study, a set of traditional Asian daggers called kris or keris, with scarce information about their entry into museum collections, their origin, the type of material used, the date of production, etc., were analysed by Energy Dispersive X-ray Fluorescence spectrometry (EDXRF), Proton Induced X-ray Emission (PIXE) and hardness measurements. In this way, the traditional procedure of historian inspection was supplemented by the scientific approach to obtain information about the artifacts.
Keywords: analysis; azijska bodala; kris; PIXE; protonsko vzbujena rentgenska emisija; rentgenska fluorescenčna spektrometrija; sestava; trdota; XRF